Power plays power works - Fiske, John (Routledge Taylor & Francis Group, 2016)
"Drawing on a diverse set of cultural sites - from alternative talk radio forums, museums, celebrity fandom, to social problems such as homelessness - Fiske traverses the topography of the American cultural landscape to highlight the ways that ordinary people creatively construct their social identities and relationships through the use of the resources available to them, while constrained by social conditions not of their own choosing. This important analysis provides a set of critical methodological and analytical tools to grapple with the complexities and struggles of contemporary social life."--Back cover.